Carbonate chemistry of ambient (∼380 μatm) and high (∼850 μatm) CO2 sites off a volcanic CO2 vent in Vulcano island, Italy - Spatafora, Davide; Cattano, Carlo; Aglieri, Giorgio; Quattrocchi, Federico; Turco, Gabriele; Calosi, Piero; Milazzo, Marco (PANGAEA, 2023)
Carbonate chemistry measured at two CO2 sites characterized by different pCO2 regimes (high pCO2 and ambient pCO2) of Vulcano Island (year 2019). Multiple measurements of salinity, temperature (T °C) and pH were carried out daily in each experimental site (between 10:00-17:00 h) on the same day the behavioural trials were performed. A multi- parametric probe (YSI 556 MPS, YSI Inc. Yellow Springs, OH) was used to measure salinity and pH and temperature (°C). A fixed Total Alkalinity of 2500 μmol kg− 1 (assumed for this study), pHNBS temperature and salinity were used to calculate the pCO2 levels using the software CO2SYS (Pierrot et al., 2006) with dissociation constants for carbonate from Mehrbach et al. (1973) refitted by Dickson and Millero (1987), and for KSO4 from Dickson (1990).
Keywords: Behaviour; Cnidaria; CO2 seeps; Field experiment; global change; Gobiidae; predation; Risk assessment